Evolution of surface relief of epitaxial diamond films upon growth resumption by microwave plasma chemical vapor deposition. Issue 12 (4th March 2020) - Shu, G.; Ralchenko, V. G.; Bolshakov, A. P.; Zavedeev, E. V.; Khomich, A. A.; Pivovarov, P. A.; Ashkinazi, E. E.; Konov, V. I.; Dai, B.; Han, J.; Zhu, J.
Abstract : Homoepitaxial diamond growth may proceed with stops and resumptions to produce thick crystals. We found the resumption procedure to take place in a complex way, via a disturbance of step growth features, followed by the recovery after a certain time. Abstract : Homoepitaxial diamond growth may proceed with stops and resumptions to produce thick (a few millimeters or even larger) crystals or structures with different layers ( e.g., doped and intrinsic diamonds). Here, we studied the effect of interrupting and resuming the growth of single crystal diamond films by microwave plasma CVD in CH4 –H2 mixtures, with a focus on the change in the surface morphology with the process time. We found a strong impact of the transition period from a pure H2 plasma to a steady state gas composition on the surface relief evolution. The growth resumption starting from a well-ordered step structure is shown to proceed via the destruction of the steps with further recovery. The velocity of the step propagation, ∼32 μm h −1, was determined from the comparison of the step pattern images obtained after each short (30 min) deposition period. For epitaxy on a polished substrate surface, we observed the growth rate retarding very early in the process stage presumably because of the incomplete macroscopic step formation. Using photoluminescence (PL) mapping in the cross-sections of a multilayer epi-film, the depth profiles of silicon-vacancy (SiV) and nitrogen-vacancy (NV) PL intensities were found to show a modulation correlated with the growth history. These results shed light on the origin of defects on inner interfaces in diamond crystals grown in halt-resumption mode.